Credit constraints and durable consumption: A new empirical approach - Risto Herrala (Bank of Finland, 2010)
I find quantitative evidence of a significant effect for credit constraints on durable consumption during a post-deregulation consumer spending spree. The effect varied markedly across age and educational groups. Young households with low levels of education displayed high sensitivity to credit conditions. In contrast, older highly educated households were relatively immune to credit market developments.
URN:NBN:fi:bof-20140807200
Keywords: D12; D91; E21; 330; durable consumption; credit constraints; stochastic frontier analysis